Calcination Effects on Sulfuric Dissolution of Phosphate Extracted from Djebel Onk Mine (Algeria) - MIZANE, ABBES; LOUHI, ACHOUR (Asian Journal of Chemistry, 2010)
The main object of this study is to investigate the calcination effects on the dissolution of phosphate rock from the mine of Djebel Onk (Algeria) in the sulfuric acid. Using conventional methods, the yielded conversion rates of P2O5 obtained during the dissolution of both rock and calcined phosphates are compared. Initially, the phosphate rock is burned to ash at temperatures ranging from 800 to 1200 °C. Then, the quantity of P2O5 is dosed out at each calcination temperature. A maximum rate of 32.35 % by weight of P2O5 is obtained at 1000 °C. By varying the retaining time of the reagents, it is noted that the reaction of calcined phosphate with the sulfuric acid is very fast as it took only a period of 10 min to reach a conversion rate of 78.39 % into P2O5. In the case of phosphate rock, it is observed that the reaction is slower compared to the earlier one and a rate of 95.86 % by weight is attained by 1.5 h.